Aging of technical systems – literature review (Journal of Production Engineering, 2021)
The maintenance is one of the most important territories of practical vehicle engineering. For optimal management maintenance decisions one of the most important matter to know momentary technical state of given system. In this paper literature of aging of technical systems is studied briefly. We found 2 major topics. They are maintenance management and mathematical modelling. These and their connections with other matter was widely studied in the field of aging. In this review we comparatively discuses all the methods and their theories. It will be very helpful for other readers to choose any methods to carry out better results.
Keywords: aging; maintenance management; mathematical modelling